2021
DOI: 10.2147/ott.s290284
|View full text |Cite
|
Sign up to set email alerts
|

The ALDOA Metabolism Pathway as a Potential Target for Regulation of Prostate Cancer Proliferation

Abstract: Background: ALDOA plays an essential role in cancer progression in different human cancers; however, its function has not been understood in prostate cancer (PCa). Methods: Associations of ALDOA expression with clinicopathological features and patient prognosis in PCa were evaluated based on data obtained from the Taylor database and our clinical tissue microarray. The potential roles of ALDOA in malignant progression were verified using a series of in vivo and in vitro experiments after stable ALDOA overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…ALDOA and POU5F1 (also called OCT4) were the top two molecules identified ( Figure 4(d) ). Both ALDOA and OCT4 are metabolic proteins associated with glucose intake [ 25 , 26 ] and are crucial for cancer progression [ 27 , 28 ]. It has been suggested that ALDOA and OCT4 regulate metabolism-related proteins, such as HK2 and PKM2 [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALDOA and POU5F1 (also called OCT4) were the top two molecules identified ( Figure 4(d) ). Both ALDOA and OCT4 are metabolic proteins associated with glucose intake [ 25 , 26 ] and are crucial for cancer progression [ 27 , 28 ]. It has been suggested that ALDOA and OCT4 regulate metabolism-related proteins, such as HK2 and PKM2 [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hsa_circ_103973 promotes cervical cancer progression through miR-335 [42]. As a proven target of miR-335, ALDOA and OCT4 regulate glucose metabolism and homeostasis [25,26,43]. With the increasing incidence of drug-tolerant in various breast cancer subtypes [44][45][46], new therapies or diagnostics could be developed for distant metastasis based on the relationship between circKIF4A and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, glycolysis increases with decreased oxygen availability, offering a benefit for growth [ 29 ]. Recent studies have demonstrated that the key enzyme ALDOA (aldolase A) in glycolysis is a cancer-related gene according to the Human Protein Atlas information [ 30 ]. HIF1A was also reported to upregulate ALDOA expressions under hypoxic conditions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of GCLC was reported in multiple types of tumors (43,44). ALDOA is coding genes of Aldolase A that involves in the glycolysis of cancer cells (45). It is related to the poor survival of various types of tumors, including pancreatic cancer, osteosarcoma, and LUSC (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%